Place attachment and spending preferences in a local public park system: The case of corporate sponsorship. (15th March 2018) - Pitas, Nicholas A.; Mowen, Andrew J.; Graefe, Alan R.; Kyle, Gerard T.
Abstract: In light of reduced public spending on local park and recreation services, corporate sponsorship has received attention as an effective, but potentially controversial, alternative funding strategy. Visitor place attachment may significantly influence the acceptability of specific spending practices of sponsorship revenue. The present study examines the influence of park users' place attachment on the relationship between their attitude toward corporate sponsorship and a recreation agency's specific spending decisions. It was hypothesized that place attachment would moderate the relationship between attitudes toward corporate sponsorship and support for spending revenue on facilities and on programming. Analysis showed that place identity was a significant moderator, strengthening the relationship between attitudes toward sponsorship and spending support for programming. As place identity increased and attitudes toward sponsorship became more positive, support for spending on programming increased concomitantly. Implications for future research and practice are discussed.